ANALISIS ANALISIS TREND HARGA CABAI RAWIT ( CAPSICUM FRUTESCENS L ) DI KABUPATEN OGAN KOMERING ULU (JASEP, 2018)
This study analyzes of the price trend of cayenne pepper in the distric Ogan Komering Ulu guided. The purpose of this research is to analyze the price trend of cayenn pepper in regency of Ogan Komering Ulu five years to come. The research method used in this research is literature study method, that is the method used for research type using secondary data. The data cellected in this research are time series data, production data of cayenne pepper and price data of cayenne pepper in regency ogan komering ulu obtained from agricultured department of food crops and horticulture and central statistics agency of ogan komering ulu the method of processing and analyis of data on the price trend of cayenne pepper in regency ogan komering ulu using linear trend analysis of least squares method. Based on the analysis of the price trend of cayenne pepper for the next five years, the year 2017-year 2021 has increased.